The Influence of Pesantren Curriculum Implementation on Student Discipline: A Quantitative Study at MTsS Maghfirah, Bogor - Muhammad Nur Basit; Abdan (CV. Kalimasada Group, 2025)
This study examined the influence of pesantren curriculum implementation on student discipline at MTsS Maghfirah Islamic Boarding School (MILBoS), Bogor. A quantitative associative approach with a correlational design was employed, involving 83 students selected through proportionate stratified random sampling from a population of 475. Data were collected using a validated and reliable 40-item questionnaire and analyzed through descriptive statistics, prerequisite tests, Pearson product-moment correlation, simple linear regression, and a partial t-test. The implementation of the pesantren curriculum was categorized as good (M = 68.81), while student discipline was fairly good (M = 66.61). A strong positive relationship was found between the two variables (r = 0.699), with a statistically significant effect (t = 8.788, p < 0.001). The coefficient of determination (R2 = 0.488) indicated that 48.8% of the variance in student discipline was explained by curriculum implementation, yielding the regression model Y = 15.566 + 0.742X. The findings indicate that a structured and habituative pesantren curriculum significantly enhances student discipline, providing empirical evidence supporting its role in strengthening character development in Islamic boarding schools. These results offer institutional leaders an evidence base for prioritizing curriculum implementation quality as a strategic lever for improving student discipline.